The conflict between the papacy and the Holy Roman Empire during the early Avignon era, 1300-1360 - Renna, Thomas (Lewiston : The Edwin Mellen Press, 2013)
A valuable book presenting readers with an overarching view of the literature produced during a time of intense conflict between the papacy and secular rulers just before and during the Avignon Papacy from 1300-1360 A.D. Implicit in the discussions is the question of the nature of the Church itself and its role in society.
Chapter Eight -- Lupold of Bebenberg, Conrad of Megenburg, Alvarus Pelagius: A New SynthesisConclusion; Bibliography; Index.
Description based on print version record.
Keywords: Papacy -- History -- 1309-1378.; Church and state -- Holy Roman Empire; Church history -- Middle Ages, 600-1500.; RELIGION / Christian Theology / Ecclesiology; Electronic books